The Role of Serum Low-Density Lipoprotein and Gamma-Glutamyl Transferase Levels in Missed Miscarriage among Women over 35: A Case-Cohort Study - Ni Zhou; Yue-min Hou; Miao-yan Ma; Yan-hua Qi; Xiao-ning Lu; Jin-fang Wu (Clinical and Experimental Obstetrics & Gynecology)
Background: Current research on the characteristics of missed miscarriage (MM) in women over the age of 35 is limited. This study investigates the role of serum metabolites for MM among women in this age group. Methods: This study included a total of 80 women over the age of 35 who experienced MM and 66 women over the age of 35 with healthy pregnancies, conducted between March 2021 and June 2022. General information, including age, gestational age, body mass index (BMI), gravidity, live birth, history of spontaneous miscarriage, drug or radiation exposure, occupation, and pregnancy-related complications, was collected. The recorded serum indicators included total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), lactate dehydrogenase (LDH), and gamma-glutamyl transferase (GGT). Potential risk factors for MM in the case-cohort were identified using univariate and multivariate logistic regression analyses. The diagnostic relevance of serum markers for MM was examined through receiver operating characteristics (ROC) curve analysis. Results: The incidence of MM increased with higher LDL and GGT values (p < 0.05). The area under the curve (AUC) was 0.709 for LDL and 0.792 for GGT. An LDL value >2.31 identified MM with a sensitivity of 72.5% and a specificity of 66.7%, while a GGT value >15.5 identified MM with a sensitivity of 78.8% and a specificity of 72.7%. However, the combined diagnostic accuracy of the two indicators was superior of that of either single index (AUC = 0.880, sensitivity = 92.5%, specificity = 72.7%; Z = 4.238, 2.813, p < 0.001, p < 0.01). Conclusions: In women over the age of 35, serum LDL and GGT are high-risk factors for MM, each potentially playing a significant role in its diagnosis. The combination of these two markers may improve diagnostic accuracy. The preliminary results of this study warrant further investigation through a well-designed, multicenter prospective study.